NOT ONLY HUMOUR FOR THE CZECHS, OR IN OTHER WORDS, IDENTITY PROBLEMS - KARDYNI-PELIKÁNOVÁ, KRYSTYNA (Porównania, 2015)
The article presents speeches of Czech publicists, sociologists and culture studies specialists on the Czech social and individual identity at the turn of the 21st century and their observations on two national identities, Czech and Polish, frequently based on stereotypes. It provides different Czech and foreign interpretations of two protagonists: the historical, Jan Hus, and the fictional and literary, Josef Švejk as symbols (icons) of the dual Czechhood.